PATHOGENESIS OF THE DEVELOPMENT OF ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES IN PATIENTS WITH SARS-CoV-2 - Bobokulova, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The problem of diagnosis and treatment of acute purulent-destructive lung diseases is still relevant due to the continuing high frequency of unsatisfactory outcomes. To date, the high effectiveness of such methods as increasing the effectiveness of antibiotic therapy with the use of intravascular (into the pulmonary artery, into the bronchial artery) administration of drugs and intracavitary (transthoracic, endobronchial) ways of sanitation of purulent-destructive foci in the lungs has already been proven. The main problems that need to be solved are the identification of patients at risk of developing acute purulent-destructive lung diseases and the development of more effective approaches to their treatment. One of these risks today is ventilator-associated pneumonia against the background of SARS-CoV-2. This manuscript is devoted to a review of the literature on the pathogenesis of the development of acute purulent-destructive lung diseases in patients with SARS-CoV-2